OPTIMALISASI IMPLEMENTASI AKAD MUDHARABAH DALAM SISTEM BAGI HASIL UNTUK MENINGKATKAN PENDAPATAN DI TOKO KELONTONG MADURA: STUDI KASUS PADA TOKO BINTANG TSURAYYAH JOMBANG - Nuri Alfiani, Febi; Widad, Romzatul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Grocery stores (toko kelontong) are common micro-enterprises in Madura, often managed by individuals or families with limited capital. In this context, the implementation of the mudharabah contract as a profit-sharing system can serve as a solution to increase the store owners’ income. Through the mudharabah contract, capital owners (shahibul mal) and managers (mudharib) collaborate by sharing both risks and profits from the business. This study aims to examine how the mudharabah contract can be implemented in the profit-sharing system of Madura’s grocery stores. The research explores the impact of this system on increasing income, while also identifying challenges and opportunities faced by business owners. A qualitative approach was used, employing in-depth interviews with grocery store owners, investors, and other relevant parties. The agreed profit-sharing ratio is 50-50 between the capital owner and the manager. Challenges include competition among stores, dishonesty among managers, and unstable income, while supporting factors include mutual benefits for both parties and satisfactory earnings. The profit-sharing system in Madura's grocery business involves the mudharib running the store, while the shahibul mal entrusts the business to the mudharib. The profit-sharing is calculated based on the store's profit, minus operating expenses such as purchase costs, rent, electricity, waste management, and damages.